“THE ROLE OF URBAN LANDSCAPE IN ENHANCING SAMARKAND’S CULTURAL AND VISUAL IDENTITY” - Nuriddinova Diyora Jasurbek Qizi (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2026)
This article explores the role of urban landscape design in strengthening Samarkand’s cultural and visual identity. The study focuses on how historical landmarks, public spaces, gardens, and modern urban infrastructure interact to create a cohesive cityscape. The research emphasizes strategies for integrating aesthetic, cultural, and functional elements to maintain the city’s heritage while supporting contemporary urban development and tourism.